TEACHERS PERCEPTION ON ROLE OF ARTIFICIAL INTELLIGENCE IN HIGHER EDUCATION- AN EMPIRICAL STUDY - Shetty .K, Udaya; Hegde .S, Vidyadhara (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Since artificial intelligence became widespread, schooling has evolved. AI shows several ways to improve educational institutions and teaching. AI aids higher education institutions in homework evaluation, exam grading, research paper arrangement, visual communication enhancement, and administrative management. AI can recognize student characteristics and provide customized learning tools. AI deployment helps higher education institutions design curriculums that match student interests and real-life settings, making them more inventive. AI's strategic role in advancing educator skills and educational excellence is described above. Appropriate AI technology gives educators, students, and visionaries full control to alter education and improve human capacities. Multiple Indian and foreign studies show that higher education institutions gain much from artificial intelligence, despite its many uses. Academic institutions will use AI systems to teach students how to perceive AI. During this developing era, educators must learn how to incorporate this technology into their lessons. AI technology enables unique student engagement strategies that improve learning. Teachers must receive annual training and digital education to integrate AI academically. AI in higher education need positive teaching attitudes and encouragement to achieve. This empirical study examines higher education professors' views on AI integration. Research seeks to understand the organizational structure needed for higher education AI integration.